2006
DOI: 10.1111/j.1752-1688.2006.tb03824.x
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECTS OF VEGETATION AND SOIL TYPE ON STREAMBANK EROSION, SOUTHWESTERN VIRGINIA, USA1

Abstract: The goal of this research was to evaluate the relative effects of root density, freeze/thaw cycling, and soil properties on the erodibility and critical shear stress of streambanks. The erodibility and critical shear stress of rooted bank soils were measured in situ at 25 field sites using a submerged jet test device; several soil, vegetation, and stream chemistry characteristics shown to influence soil erosion were also assessed. Multiple linear regression analysis was conducted to determine those factors tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
143
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(160 citation statements)
references
References 31 publications
14
143
1
2
Order By: Relevance
“…Gyssels et al (2005) showed that while dense root systems produced by a mix of small trees, shrubs, and grasses were important in maintaining slope stability, shallow dense root networks produced by grasses appear to be more effective in protecting soils from water erosion by concentrated flow. It is also the case that fine and small roots (0.5-2.0 mm in diameter) at deeper soils (root depth>30 cm) with high tensile strength, especially for tree species, are more efficient in supporting stream bank stability (Davidson et al 1989;Wynn et al 2004;Wynn and Mostaghimi 2006). The grasses and shrubs are optimum cover types for slope stabilization largely due to their large numbers of small, strong roots (Li.…”
Section: Discussionmentioning
confidence: 99%
“…Gyssels et al (2005) showed that while dense root systems produced by a mix of small trees, shrubs, and grasses were important in maintaining slope stability, shallow dense root networks produced by grasses appear to be more effective in protecting soils from water erosion by concentrated flow. It is also the case that fine and small roots (0.5-2.0 mm in diameter) at deeper soils (root depth>30 cm) with high tensile strength, especially for tree species, are more efficient in supporting stream bank stability (Davidson et al 1989;Wynn et al 2004;Wynn and Mostaghimi 2006). The grasses and shrubs are optimum cover types for slope stabilization largely due to their large numbers of small, strong roots (Li.…”
Section: Discussionmentioning
confidence: 99%
“…For example, progress in quantifying fluvial erosion (i.e., the removal of bank material by the action of hydraulic forces) has included the development and application of specific techniques for measuring in situ the erodibility parameters of the bank sediments [Tolhurst et al, 1999;Hanson and Simon, 2001;Wynn and Mostaghimi, 2006;Clark and Wynn, 2007], as well as methods to model the near-bank flow field using computational fluid dynamics (CFD) and other techniques [Darby et al, 2004;Smith, 2006a, 2006b;McBride et al, 2007;Julian and Torres, 2006;Papanicolaou et al, 2007]. With respect to mass failure, recent studies have focused on two main topics:…”
Section: Introductionmentioning
confidence: 99%
“…As suggested by previous research [13,29,[48][49][50], variability observed in erodibility parameters can be attributed to soil heterogeneity and subaerial processes. When compared to other studies [13,29,[48][49][50], less variability in erodibility parameters was observed along FC-FM and FC-WC.…”
Section: Variability Of Erodibility Parametersmentioning
confidence: 80%